Cemented or uncemented hemiarthroplasty for intracapsular hip fracture - Fernandez, MA; Achten, J; Parsons, N; Griffin, XL; Png, M-E; Gould, J; McGibbon, A; Costa, ML (Massachusetts Medical Society, 2022)
BACKGROUND Controversy exists over the use of bone cement in hip fractures treated with hemiarthroplasty. Only limited data on quality of life after cemented as compared with modern uncemented hemiarthroplasties are available.